From darkness to light writers in museums 1798-1898 - Mamoli Zorzi, Rosella; Manthorne, Katherine; Open Book Publishers; International Conference "From darkness to light : writers in museusm 1798-1898" (2016 : Venice, Italy) (Open Book Publishers, 2019)
"From Darkness to Light explores from a variety of angles the subject of museum lighting in exhibition spaces in America, Japan, and Western Europe throughout the nineteenth and twentieth centuries. Written by an array of international experts, these collected essays gather perspectives from a diverse range of cultural sensibilities. From sensitive discussions of Tintoretto's unique approach to the play of light and darkness as exhibited in the Scuola Grande di San Rocco in Venice, to the development of museum lighting as part of Japanese artistic self-fashioning, via the story of an epic American painting on tour, museum illumination in the work of Henry James, and lighting alterations at Chatsworth (to name only a few topics) this book is a treasure trove of illuminating contributions. The collection is at once a refreshing insight for the enthusiastic museum-goer, who is brought to an awareness of the exhibit in its immediate environment, and a wide-ranging scholarly compendium for the professional who seeks to proceed in their academic or curatorial work with a more enlightened sense of the lighted space."--Publisher's website.
Acknowledgments -- Notes on Contributors -- Introduction: From Darkness to Light: Writers in Museums 1798-1898 / Rosella Mamoli Zorzi and Katherine Manthorne -- Part I: On Light. 1. Tintoretto: An Unexpected Light. Lightnings, Haloes, Embers and Other Glowing Lights / Melania G. Mazzucco ; 2. The Artificial Lighting Available to European and American Museums, 1800-1915 / David E. Nye -- Part II: On Light at the Scuola Grande di San Rocco and in Venice. 3. Tintoretto in San Rocco Between Light and Darkness / Maria Agnese Chiari Moretto Wiel ; 4. John Ruskin and Henry James in the Enchanting Darkness of the Scuola Grande di San Rocco / Rosella Mamoli Zorzi ; 5. Light at the Scuola Grande di San Rocco / Demetrio Sonaglioni ; 6. The Light in the Venice Ducal Palace / Camillo Tonini ; 7. Latent in Darkness: John Ruskin's Virtual Guide to the Academy of Fine Arts in Venice / Emma Sdegno ; 8. Venice, Art and Light in French Literature: 1831-1916 / Cristina Beltrami -- Part III: On Light in American Museums. 9. One Hundred Gems of Light: The Peale Family Introduces Gaslight to America / Burton K. Kummerow ; 10. Illuminating the Big Picture: Frederic Church's Heart of the Andes Viewed by Writers / Katherine Manthorne ; 11. Italian Genius in American Light: The James Jackson Jarves Collection at Yale / Kathleen Lawrence ; 12. Shedding Light on the History of Lighting at the Isabella Stewart Gardner Museum / Holly Salmon ; 13. Seeing Beauty: Light and Design at the Freer Gallery, ca. 1923 / Lee Glazer -- Part IV: On Light in Museum and Mansions in England, France, and Spain. 14. Lighting up the Darkness: The National Gallery, London / Sarah Quill ; 15. Sir John Soane / Helen Dorey ; 16. Chatsworth, a Modern English Mansion / Marina Coslovi ; 17. Daylight and Gold: In the Galleries With Henry James / Paula Deitz ; 18. Remarks on Illumination in Nineteenth-Century American Travel Writings on Madrid's Prado Museum / Pere Gifra-Adroher -- Part V: On Light in Italian Museums. 19. To Look (and to See) in the Nineteenth Century: At the Uffizi and Elsewhere / Cristina Acidini -- 20. Ways of Perceiving: The Passionate Pilgrims' Gaze in Nineteenth-Century Italy / Margherita Ciacci ; 21. 'In the Quiet Hours and the Deep Dusk, These Things too Recovered Their Advantage': Henry James on Light in European Museums / Joshua Parker ; 22. 'Shedding Light on Old Italian Masters': Timothy Cole's Series for the Century / Page S. Knox ; 23. 'Into the Broad Sunlight': Anne Hampton Brewster's Chronicle of Gilded Age Rome / Adrienne Baxter Bell -- Part VI: On Light in Museums in Japan. 24. In Praise of Shadows: Ernest Fenollosa and the Origins of Japanese Museum Culture / Dorsey Kleitz and Sandra Lucore -- Postscript. 25. Premonitions: Shakespeare to James / Sergio Perosa ; 26. The Museum on Stage: From Plato's Myth to Today's Perception / Alberto Pasetti Bombardella ; 27. Time and Light / Antonio Foscari -- Bibliography -- List of Illustrations.
"This book originated from the international conference "From darkness to light : writers in museusm 1798-1898", organized by the Venice Committee of the Dante Alighieri Society, the Fondazione Musei Civici Veneziani, the Scuola Grande di San Rocco, and the Graduate School of the City University of New York, which took place in Venice between 27-29 April 2016"--Introduction, unnumbered page 1.
Available through Open Book Publishers.
Includes bibliography (pages 333-353).
Mode of access: World Wide Web.
Keywords: Art museum visitors -- Attitudes; Art museums -- Lighting -- History; Art -- Exhibition techniques -- History; Authors -- 18th century -- Attitudes; Authors -- 19th century -- Attitudes; Museum visitors -- Attitudes; Museums -- Lighting -- History